Simulation and realization of simultaneous operation of all-optical NOR, AND, XNOR gates using semiconductor optical amplifiers - Son, Chang Wan; Kim, Sang H; Jhon, Young Min; Byun, Young Tae; Lee, Seok; Woo, Deok Ha; Kim, Sun Ho; Yoon, T.-H. (COIN-NGNCON 2006 - The Joint International Conference on Optical Internet and Next Generation Network, 2006)
We simulated and demonstrated all-optical multi-functional logic gates for simultaneous operations at 10 Gbps. All-optical XNOR, NOR and AND operations are simultaneouslv realized in this work. ？2006 OSIA.